Pathophysiology of immune thrombocytopenia. Issue 5 (September 2018) - Li, June; Sullivan, Jade A.; Ni, Heyu
Abstract : Purpose of review: Immune thrombocytopenia (ITP) is a common autoimmune bleeding disorder with as of yet, no established clinical prognostic or diagnostic biomarkers. Patients frequently experience a markedly decreased quality of life and may be at risk for severe/fatal haemorrhage. Here, we address discoveries in the pathogenesis of ITP, and novel therapeutic strategies in mouse models and human patients. Consolidation of these findings should be important in providing insight to establish future prognostic protocols as well as cutting-edge therapeutics to target refractory ITP. Recent findings: It is unknown why a significant portion of ITP patients are refractory to standard treatments. Recent findings suggest distinct heterogeneity in ITP including antibody-mediated platelet activation, Fc-independent desialylated platelet clearance, attenuation of platelet-mediated hepatic thrombopoietin generation, and decreased CD8 + T-suppressor generation. These mechanisms may partially explain clinical observations of increased refractoriness to standard therapies targeting classical Fc-dependent pathways. Moreover, these have initiated investigations into platelet desialylation as a diagnostic/prognostic marker and therapeutic target. Summary: Recent evidence of distinct ITP pathophysiology has opened new exploratory avenues for disease management. We will discuss the utility of investigations into these mechanisms of ITP and its potential impact in our understanding of pathogenesis and future treatment strategies.